Heterocyclic Cathinones as Inhibitors of Kynurenine Aminotransferase II-Design, Synthesis, and Evaluation - Michal Maryška; Lucie Svobodová; Wim Dehaen; Martina Hrabinová; Michaela Rumlová; Ondřej Soukup; Martin Kuchař (MDPI AG, 2021)
Kynurenic acid is a neuroprotective metabolite of tryptophan formed by kynurenine aminotransferase (KAT) catalyzed transformation of kynurenine. However, its high brain levels are associated with cognitive deficit and with the pathophysiology of schizophrenia. Although several classes of KAT inhibitors have been published, the search for new inhibitor chemotypes is crucial for the process of finding suitable clinical candidates. Therefore, we used pharmacophore modeling and molecular docking, which predicted derivatives of heterocyclic amino ketones as new potential irreversible inhibitors of kynurenine aminotransferase II. Thiazole and triazole-based amino ketones were synthesized within a SAR study and their inhibitory activities were evaluated in vitro. The observed activities confirmed our computational model and, moreover, the best compounds showed sub-micromolar inhibitory activity with 2-alaninoyl-5-(4-fluorophenyl)thiazole having IC50 = 0.097 µM.